Implementation of Regional Autonomy Law in Line with Local Culture - Sinaga, Fredrico Markus Rotua; Damayanti, Ratih (Riviera Publishing, 2025)
The law of regional autonomy is a branch of law that regulates regional authority in managing its own government affairs based on the principle of decentralization. In the Indonesian constitutional system, regional autonomy aims to enhance government effectiveness, accelerate development, and provide quality services to the community by considering regional characteristics and needs. The main legal basis for regional autonomy in Indonesia is outlined in Articles 18, 18A, and 18B of the 1945 Constitution, as well as Law Number 23 of 2014 concerning Regional Government. Key concepts in regional autonomy law include the division of authority between central and regional governments, financial relationships between the two, and principles of supervision and accountability in local governance. However, regional autonomy faces challenges such as corruption at the regional level and imbalances in the implementation of central policies. Therefore, strengthening regulations and supervisory mechanisms is crucial to ensure that regional autonomy laws align with the principles of democracy, government effectiveness, and community welfare.